Społeczna odpowiedzialność biznesu w bankach spółdzielczych Unii Europejskiej – teoria i praktyka - Siudek, Tomasz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
Cooperative banks in developed countries of the European Union are social economy entities with range of social and environmental purposes. They fully realize the concept of corporate social responsibility – CSR. They stimulate local and regional socio-economic development as well as contribute significantlyt environmental protection. They also implemented the principles of CSR towards different stakeholders such as bank members, customers and employees. They are key players in EU cohesion policy.